2021
DOI: 10.3390/pr9122218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seasonal Thermal Stratification on Ammonia Nitrogen Transformation in a Source Water Reservoir

Abstract: Seasonal thermal stratification has a significant impact on water quality. In this paper, the variation of vertical distribution of ammonia nitrogen in a source water reservoir was studied, on the base of field monitoring data. The dominant factor of the variation in ammonia nitrogen is the anaerobic environment caused by the seasonal thermal stratification, which leads to the degradation of nitrogen-containing organic compounds in the sediments. To determine the rates of ammonia accumulation, an in situ exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…This internal recycling may comprise the primary mechanism for the high levels of N retention in the pond's deepest layers, where total dissolved N reaches to 775 uM. Similar ammonium accumulation trends have been noted in other highly stratified systems (Beutel, 2001;Cutrofello and Durant, 2007;Shi et al, 2021). Considering NH 4 + assimilation by phytoplankton as a secondary sink of NH4 + from the middle layer, the variations in the requisite 15 e of NH 4 + loss may actually reflect variations in the relative magnitudes of these processes.…”
Section: Model Resultssupporting
confidence: 56%
“…This internal recycling may comprise the primary mechanism for the high levels of N retention in the pond's deepest layers, where total dissolved N reaches to 775 uM. Similar ammonium accumulation trends have been noted in other highly stratified systems (Beutel, 2001;Cutrofello and Durant, 2007;Shi et al, 2021). Considering NH 4 + assimilation by phytoplankton as a secondary sink of NH4 + from the middle layer, the variations in the requisite 15 e of NH 4 + loss may actually reflect variations in the relative magnitudes of these processes.…”
Section: Model Resultssupporting
confidence: 56%
“…The concentration of NH + 4 −N in bottom water increased over time during summer and winter stratification owing to decomposition of organic matter [21,52,53]. The low DO concentration at a depth of 7 m in August (Figure 4c) can be explained as similar to the thermal classification and summer stratification [10]. Jaeger [54] reported that the lowest DO concentrations were observed during summer in the hypolimnion (6-10 m depth) and surface sediments of a small urban lake, Lake Krupunder in Germany.…”
Section: Dynamic Of the Din Profile In Lake Bulanmentioning
confidence: 79%
“…Small lakes at temperate latitudes provide important indicators of the impacts of anthropogenic activity and global warming on water quality, which include the duration of thermal stratification in summer and lake mixing regime [9,10]. Stable stratification prevents the exchange of water between the surface and bottom layers and has a significant impact on the physical and chemical parameters of the water quality [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation